2003
DOI: 10.1182/blood-2002-03-0853
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of donor splice site mutations accounting for congenital afibrinogenemia reflects order of intron removal in the fibrinogen alpha gene (FGA)

Abstract: Congenital afibrinogenemia (Mendelian Inheritance in Man #202400) is a rare, autosomal recessive disorder characterized by the complete absence of circulating fibrinogen. Our recent studies on the molecular basis of the disease showed that the most common genetic defect is a donor splice mutation in fibrinogen alpha gene (FGA) intron 4, IVS4؉1G>T. Two other FGA donor splice mutations, in intron 1 (IVS1؉3A>G) and intron 3 (IVS3؉1_؉4delGTAA), were identified in afibrinogenemia patients. Because it was impossible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 28 publications
1
38
0
2
Order By: Relevance
“…There is strong evidence to support the theory that the order of intron removal and speed of splicing are important determinants of mRNA transcripts with multiple exon skipping. [21][22][23] On this basis, our results confirm the proposal that the double exon skipping represents an example of mutually inclusive exons in which the unusually large size of one exon is contingent to the recognition of the following exon by the splicing mechanism. 21 Otherwise, increasing evidence shows that RNA specific secondary structure influences the splicing machinery and plays an important role in exon definition for particular transcripts.…”
Section: Molecular Basis For the Spectrin Deficiencysupporting
confidence: 76%
“…There is strong evidence to support the theory that the order of intron removal and speed of splicing are important determinants of mRNA transcripts with multiple exon skipping. [21][22][23] On this basis, our results confirm the proposal that the double exon skipping represents an example of mutually inclusive exons in which the unusually large size of one exon is contingent to the recognition of the following exon by the splicing mechanism. 21 Otherwise, increasing evidence shows that RNA specific secondary structure influences the splicing machinery and plays an important role in exon definition for particular transcripts.…”
Section: Molecular Basis For the Spectrin Deficiencysupporting
confidence: 76%
“…These mutations all affect the conserved donor splice site consensus sequence, with the exception of the FGB c.9581 13C4T mutation that creates a novel donor splice site . For some aberrant splicing with exon skipping [Attanasio et al, 2003;Margaglione et al, 2000], intron inclusion , or usage of cryptic splice sites has been demonstrated. As for other genetic diseases, mutations at acceptor splice sites are less frequent; only two have been identified so far; i.e., one in FGG c.124-3C4G [NeermanArbez et al, 2001] and one in FGB c.1245-1G4C [Horellou et al, 2006].…”
Section: Splice-site Mutationsmentioning
confidence: 99%
“…Reports on autosomal recessive disorder with a molecular base of congenital afibrinogenemia indicated association with the aberrant splicing caused by inactivation of physiologic splice sites [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Most abnormal RNA splicing was reported to occur near the donor splice site, with five kinds of mutation in FGA, four in FGB and three in the IVS3 +1 to +4 deletions, which were another FGA donor splice site mutation, showed exon 3 skipping in 99% of transcripts, and exon 2 and 3 skipping in 1% of transcripts [23].…”
Section: Discussionmentioning
confidence: 99%
“…Most abnormal RNA splicing was reported to occur near the donor splice site, with five kinds of mutation in FGA, four in FGB and three in the IVS3 +1 to +4 deletions, which were another FGA donor splice site mutation, showed exon 3 skipping in 99% of transcripts, and exon 2 and 3 skipping in 1% of transcripts [23]. On the other hand, mRNAs from FGB IVS6Δ4b and FGG IVS3-2G, the mutations of both of which were located in acceptor splice sites, showed no splicing out of intron 6 and intron 7 in the Bβ-chain or of intron 3 in the γ-chain, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation